Application of Intranasal Administration in the Delivery of Antidepressant Active Ingredients - Zhiyu Jin; Yu Han; Danshen Zhang; Zhongqiu Li; Yongshuai Jing; Beibei Hu; Shiguo Sun (Pharmaceutics, 2022)
As a mental disease in modern society, depression shows an increasing occurrence, with low cure rate and high recurrence rate. It has become the most disabling disease in the world. At present, the treatment of depression is mainly based on drug therapy combined with psychological therapy, physical therapy, and other adjuvant therapy methods. Antidepressants are primarily administered peripherally (oral and intravenous) and have a slow onset of action. Antidepressant active ingredients, such as neuropeptides, natural active ingredients, and some chemical agents, are limited by factors such as the blood–brain barrier (BBB), first-pass metabolism, and extensive adverse effects caused by systemic administration. The potential anatomical link between the non-invasive nose–brain pathway and the lesion site of depression may provide a more attractive option for the delivery of antidepressant active ingredients. The purpose of this article is to describe the specific link between intranasal administration and depression, the challenges of intranasal administration, as well as studies of intranasal administration of antidepressant active ingredients.